2014
DOI: 10.1111/jzo.12159
|View full text |Cite
|
Sign up to set email alerts
|

Seeing through the skin: dermal light sensitivity provides cryptism in moorish gecko

Abstract: Concealment by means of colour change is a pre-eminent deceptive mechanism used by both predators and prey. The moorish gecko Tarentola mauritanica is able to blend into the background by either darkening or paling according to the substrate darkness. Here we examined the functioning of background perception in moorish gecko. We experimentally excluded the involvement of melanophore-stimulating hormone in camouflage. Blindfolded individuals change their colour consistently with the background. Surprisingly, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…There are at least three major groups of opsins: the r-opsins, c-opsins and Go/RGR (retinal G-protein-coupled receptor) opsins (Porter et al, 2012;Feuda et al, 2012). While c-opsins are typically thought to detect light in vertebrate eyes and r-opsins in invertebrate eyes, various opsins are expressed in the skin of many animals (Ramirez et al, 2011), and opsins have been localized to receptors dispersed across the body of animals from multiple phyla, including cnidarians, echinoderms, annelids and vertebrates (Plachetzki et al, 2012;Raible et al, 2006;Backfisch et al, 2013;Bellono et al, 2013;Fulgione et al, 2014). Because opsins are known to function as light receptors, the cells that express opsin may be dispersed light sensors that could underlie some lightmediated behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…There are at least three major groups of opsins: the r-opsins, c-opsins and Go/RGR (retinal G-protein-coupled receptor) opsins (Porter et al, 2012;Feuda et al, 2012). While c-opsins are typically thought to detect light in vertebrate eyes and r-opsins in invertebrate eyes, various opsins are expressed in the skin of many animals (Ramirez et al, 2011), and opsins have been localized to receptors dispersed across the body of animals from multiple phyla, including cnidarians, echinoderms, annelids and vertebrates (Plachetzki et al, 2012;Raible et al, 2006;Backfisch et al, 2013;Bellono et al, 2013;Fulgione et al, 2014). Because opsins are known to function as light receptors, the cells that express opsin may be dispersed light sensors that could underlie some lightmediated behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…This may arise owing to comparisons with information from the chromatophore cells, which are also sensitive to light (Kingston et al, 2015;Ramirez and Oakley, 2015). Other recent work has shown that some geckos can change color to match the background when their eyes are covered, but not when their flanks were covered (which seemingly contain opsins; Fulgione et al, 2014). Further work on the role of extra-ocular light detection in guiding color change is needed.…”
Section: How Does Color Change and Plasticity Work?mentioning
confidence: 99%
“…One such investigation showed that Moorish geckos (Tarentola mauritanica) exhibit the same skin darkening response when placed on a black background, irrespective of whether the eyes were covered or not. By contrast, no color change was observed when the thorax was obscured, suggesting that light detection occurs in this region (Fulgione et al, 2014). Subsequent molecular and histological analyzes revealed that a light sensitive visual pigment was present in the skin tissues of T. mauritanica and showed higher levels of expression in the flanks than on the back or belly (Fulgione et al, 2014).…”
Section: Melanophore Responses To Environmental Lightmentioning
confidence: 99%